SYNTHESIS AND IN VITRO EVALUATION OF Ni (II) COMPLEXES OF SALICYLALDIMINE - M. ABIRAMI; V. NADARAJ (International Journal of Pharma and Bio Sciences, 2014)
Schiff bases and their metal complexes are very important in medicinal and pharmaceutical fields because of their wide spectrum of biological activities. Transition metal complexes derived from the Schiff base ligands with biological activity have been widely studied. A series of Ni (II) complexes were prepared by the reaction of salicyldimine with Nickel Oxide at room temperature. The chemical structures of metal complexes were confirmed by spectroscopic analysis and all of the compounds were evaluated for their antimicrobial properties. All the Ni (II) complexes have been found to exhibit moderate or good activity against most bacteria and fungi species.